Adsorption of phosphate from domestic wastewater treatment plant efﬂuent onto the laterites in a hydrodynamic column - Fulazzaky, Mohamad Ali; Khamidun, Mohd Hairul; Md Din, Mohd Fadhil; Mohd Yusoff, Abdull Rahim (Elsevier Science Ltd, 2014)
High concentration of phosphate (PO43